Query Expansion Pada Sistem Temu Kembali Informasi Dokumen Jurnal Berbahasa Indonesia Menggunakan Metode BM25 - Faradila Puspa Wardani; Indriati Indriati; Bayu Rahayudi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer (J-PTIIK) is a collection of scientific papers from the research Faculty of Computer Science's students, Universitas Brawijaya. In each journal there is an abstract section which is a summary of the entire contents of the scientific work document, which contains concepts, problem statements, approaches, and conclusions that are arranged. The number of journals contained in J-PTIIK is very large, therefore a document search system is needed to facilitate users in finding journal documents, a search system that implements an Information Retrieval (IR). To minimize the results of returning documents that are not relevant to the IR, query techniques can be applied, called query expansion techniques. Application of query expansion can be done by using BM25 method. BM25 is an IR that is used to sort the results of the relevance documents to the query that user want to search. This research was conducted by aiming to see the results of query expansion in information retrieval of Indonesian journal using BM25 method. The result, when adding words for queries as many as 4 words, the Precision @ K value increases by an average of 0.492.